1998
DOI: 10.1037/0022-0167.45.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of serendipity: Career paths of prominent academic women in counseling psychology.

Abstract: Consensual qualitative research was used to investigate the impact of chance events on the career choices of prominent academic women in counseling psychology and to examine the contextual factors surrounding the chance events. The results suggest that chance events affected career choices most often by changing women's career paths altogether or by altering their self-concepts. The results also suggest that both internal characteristics (e.g., ability to take risks, self-confidence, etc.) and external factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 62 publications
1
83
0
2
Order By: Relevance
“…Division into groups was suggested by Hill et al (1997Hill et al ( , 2005 and has been done in other CQR studies (e.g., Knox, Burkard, Johnson, Suzuki, & Ponterotto, 2003;Williams, Soeprapto, Touradji, Hess, & Hill, 1998). As shown in Table I, the eight supervisees in the good supervision group compared with the six supervisees in the problematic supervision group were significantly more satisfied with their supervision (M=21.…”
Section: Categorization Into Good and Problematic Supervisory Relatiomentioning
confidence: 73%
“…Division into groups was suggested by Hill et al (1997Hill et al ( , 2005 and has been done in other CQR studies (e.g., Knox, Burkard, Johnson, Suzuki, & Ponterotto, 2003;Williams, Soeprapto, Touradji, Hess, & Hill, 1998). As shown in Table I, the eight supervisees in the good supervision group compared with the six supervisees in the problematic supervision group were significantly more satisfied with their supervision (M=21.…”
Section: Categorization Into Good and Problematic Supervisory Relatiomentioning
confidence: 73%
“…Such examples were included most often when two groups were being compared (e.g., problematic vs. unproblematic events). Some have also used a composite example (e.g., Williams et al, 1998) that combines results across cases to provide a narrative sense of the average participant without revealing confidential material about any single participant. We highly recommend the use of such illustrative case examples because they help integrate the results and provide a rich picture of the phenomenon (see Ladany et al, 1997, for a good example).…”
Section: Writing Up the Results And Discussion Sectionsmentioning
confidence: 99%
“…Of the 27 studies, 22 used a combination of graduate students and postdoctoral psychologists, 2 used all postdoctoral psychologists, 2 used a combination of postdoctoral psychologists and undergraduates, and 1 used a combination of undergraduates, graduate students, and postdoctoral psychologists. From a perusal of the topics, it appears that undergraduates were used as judges when they had enough maturity or experience to handle the topics (e.g., women's career development; Williams et al, 1998), whereas more experienced people were used as judges for more abstract or difficult topics (e.g., countertransference; Hayes et al, 1998), as suggested by Moras and Hill (1991). At this point, we recommend that the sophistication level of the team members be driven by the topic.…”
Section: Composition Of Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research finds that older students' career trajectories are influenced by chance events to a greater extent than those of younger students (Hirschi 2010), and that women psychologists adopt strategies to maximise chance events (Williams et al 1998). Given that such research suggests specific ways in which chance events influence individuals' career trajectories, some of the theoretical literature advocates the incorporation of chance events into career theory.…”
Section: Traditional Models Of Career Developmentmentioning
confidence: 99%